1977
DOI: 10.1182/blood.v50.3.441.441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood donation on iron stores as evaluated by serum ferritin

Abstract: Serum ferritin was measured in 2982 blood donors. First-time male donors had a geometric mean of 127 microgram/liter and female donors 46 microgram/liter. While values were essentially constant in the women between the ages of 18 and 45, there was a rapid increase in the men between 18 and 30 years of age consistent with the establishment of iron stores during that time. Blood donation was associated with a decrease in serum ferritin. One unit per year, equivalent to an increased requirement of 0.65 mg/day, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
150
0
8

Year Published

1981
1981
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(171 citation statements)
references
References 16 publications
13
150
0
8
Order By: Relevance
“…Our data demonstrate that hepcidin/log ferritin correlates with donation frequency as a discrete and continuous variable. Thus, our findings of decreased MCV and CH r in addition to hepcidin/log ferritin provide evidence of the dynamic regulation of iron availability for erythropoiesis in concert with total body stores in frequent apheresis donors, consistent with prior evidence correlating hepcidin concentration with hemoglobin recovery in whole blood donors [28]. Methods for measuring erythroferrone, a newly described erythroid regulator of hepcidin [34], are currently being developed to assess this important parameter.…”
Section: Discussionsupporting
confidence: 86%
“…Our data demonstrate that hepcidin/log ferritin correlates with donation frequency as a discrete and continuous variable. Thus, our findings of decreased MCV and CH r in addition to hepcidin/log ferritin provide evidence of the dynamic regulation of iron availability for erythropoiesis in concert with total body stores in frequent apheresis donors, consistent with prior evidence correlating hepcidin concentration with hemoglobin recovery in whole blood donors [28]. Methods for measuring erythroferrone, a newly described erythroid regulator of hepcidin [34], are currently being developed to assess this important parameter.…”
Section: Discussionsupporting
confidence: 86%
“…Further, besides bringing the donor into contact with the health care system, where a changing hemoglobin concentration or other signs of failing health may be further investigated, frequent blood donation often causes iron depletion. [20][21][22][23] The blood donation itself may, therefore, affect both the hemoglobin concentration and the probability of early detection of a cancer. It is reassuring that the number of prior donations was almost identical in cases and controls, allowing little room for such confounding.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the endogeneous erythropoietin production during the period of mild anaemia induced by several phlebotomies is inadequate to restore haemoglobin levels before surgery [ 1-31. Recombinant human erythropoietin (rhEPO) has been administered successfully to correct the phlebotomyinduced anaemia or to increase the procurement of blood [4-81. A pre-requisite for treatment with rhEPO is the availability of a sufficient amount of iron. Repeated phlebotomy has been associated with the depletion of iron stores [9,10]. Moreover, it is known from studies in chronic renal failure patients treated with rhEPO that the acquirement of iron deficiency is the major limiting factor of the effect of rhEPO [ 1 I , 121.…”
Section: Introductionmentioning
confidence: 99%